ANALISIS KONSEPTUAL DAN IMPLEMENTATIF PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI LEMBAGA PENDIDIKAN ISLAM (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Curriculum development in Islamic Religious Education (PAI) plays a central role in determining the quality and direction of Islamic educational institutions. This study aims to analyze the conceptual and implementative dimensions of curriculum development in Islamic education, emphasizing philosophical, psychological, and sociocultural foundations. Using a qualitative descriptive method through literature review, this paper explores the theories of Islamic education scholars and national education policies that influence the development of the PAI curriculum. The results show that the development of the PAI curriculum should integrate religious values with scientific, technological, and social developments to create a holistic educational design. Implementation requires comprehensive strategies involving teachers, institutional policies, and contextual adaptation to students’ needs. This study concludes that curriculum development in Islamic educational institutions must be dynamic, integrative, and oriented toward strengthening students’ faith, morality, and intellectual competence in the era of modernization and Merdeka Belajar.